2021
DOI: 10.3389/fpsyg.2021.719692
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Dispel Neuromyths in Educational Settings—A Review

Abstract: Neuromyths are misconceptions about the brain and learning, for instance Tailoring instruction to students' preferred “learning styles” (e.g., visual, auditory, kinesthetic) promotes learning. Recent reviews indicate that the high prevalence of beliefs in neuromyths among educators did not decline over the past decade. Potential adverse effects of neuromyth beliefs on teaching practices prompted researchers to develop interventions to dispel these misconceptions in educational settings. This paper provides a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 88 publications
(155 reference statements)
2
17
0
1
Order By: Relevance
“…When analysing the teaching experience time with DHH students, we partially confirm our hypothesis, since no significant differences were found in each country, but when we look at the total teachers’ sample, we found that more years of experience does not mean fewer beliefs in neuromyths. This joint sample difference corroborates previous studies that teachers in training showed fewer false beliefs than teachers who are already working [ 40 ]. One of the explanations may be related to the fact that teachers with more experience have been more exposed to sources of information, whether they are trustworthy or not, and can access the neuroscientific literature more lightly, as looking for very specific answers and over-interpreting results, which can easily lead to extrapolations to find pedagogical recipes.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…When analysing the teaching experience time with DHH students, we partially confirm our hypothesis, since no significant differences were found in each country, but when we look at the total teachers’ sample, we found that more years of experience does not mean fewer beliefs in neuromyths. This joint sample difference corroborates previous studies that teachers in training showed fewer false beliefs than teachers who are already working [ 40 ]. One of the explanations may be related to the fact that teachers with more experience have been more exposed to sources of information, whether they are trustworthy or not, and can access the neuroscientific literature more lightly, as looking for very specific answers and over-interpreting results, which can easily lead to extrapolations to find pedagogical recipes.…”
Section: Discussionsupporting
confidence: 90%
“…inclusive educational paradigm for DHH students). Although we did not have enough data to clarify all these possible differences, this is in some way reflected in the scientific literature of both countries, which seems to serve as a reference on the teacher's practice [12,19,21,25,26,29,37,40]. Portuguese sample is the more aged one, but do not have the highest percentage in terms of experience working with DHH students.…”
Section: Plos Onementioning
confidence: 87%
See 2 more Smart Citations
“…Despite the evidence about the positive effect of neuroscience knowledge in education and the efforts to connect neuroscience and education through cognitive psychology, neuromyths persist [ 2 ]. Although there is still no evidence for a causal effect of beliefs in neuromyths and poor teaching practice [ 8 , 9 ], educational policies have already been influenced by beliefs in neuromyths, leading to large amount of resources being spent [ 10 ]. Up to date, the number of studies focused on neuroscience knowledge and belief in neuromyths are numerous, but experiments testing new ways to improve neuroscience knowledge and reduce belief in neuromyths are far fewer.…”
Section: Introductionmentioning
confidence: 99%